Effects of aggregate gradations on properties of grouted Macadam composite pavement - Husain, N.M.; Mahmud, H.B.; Karim, M.R.; Hamid, N.B.A.A. (2010)
Grouted Macadam composite pavement (GMCP) is generally a composite pavement which is manufactured by preparing a highly workable fluid mortar which is specially designed with a very high early and 28 day strength (1 day - 45 MPa, 28 day - 105 MPa) by filling the flowing fluid mortar into a very open porous asphalt skeleton (25-32 Voids in Mix - VIM). The combination of both components will produce a semi-rigid pavement or GMCP which has the best features of both rigid concrete and flexible bituminous pavement where it will replace the conventional wearing course. This paper will investigate the significance difference of GMCP produced by the 3 different aggregate gradations by Road Engineering Association of Malaysia (REAM) in volumetric properties, durability and strength. The best quality fluid grout was chosen to fill the porous asphalt skeleton and GMCP was subjected for compression test, VIM and indirect tensile test (IDT) to check on its performance. The results show that the 3 different aggregate gradations significantly affect the volumetric properties, durability and strength. Furthermore it will also help in reducing pollution and helps with the current environmental problems. Â© 2010 IEEE.